New ent-kaurene-type nor-diterpene and other compounds isolated from Annona vepretorum Mart. (Annonaceae). Issue 9 (3rd May 2023) - Araújo, Camila de Souza; Nery, Daniel Amando; Oliveira, Ana Paula de; Oliveira-Júnior, Raimundo Gonçalves de; Rolim, Larissa Araújo; Lopes, Norberto Peporine; Silva, Maria Francilene de Souza; Pessoa, Cláudia do Ó; Braz-Filho, Raimundo; Dutra, Lívia Macedo; Tavares, Josean Fechine; Abreu, Lucas Silva; et al.
Abstract: A new nor- ent -kaurene diterpene and ten other compounds were isolated from Annona vepretorum stems, including four kaurene diterpenes, three alkamides, one sesquiterpene and two steroids. Their chemical structures were elucidated using spectroscopic methods, including 1D-, 2D-NMR, and HRESIMS. The absolute configuration of compounds 1, 5, 8, 9 and 10 was confirmed by CD experiments. Compounds 1–5 and 8–10 were evaluated for cytotoxic activity using (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide) MTT method, against three human carcinoma cell lines: human colon (HCT-116), glioblastoma (SF295) and prostate (PC3). However, all isolated compounds exhibited low cytotoxic activity. Graphical Abstract: UF0001